The potential targets for metastases: a study on altered circular RNA profile in breast cancer liver metastases - Lin, Xiaorong; Hong, Shubin; Chen, Jiewen; Chen, Wenying; Wu, Zhiyong (Epigenomics, 2019)
To export the expression profile of circRNAs in breast cancer liver metastases (BCLM). RNA sequences were used to identify the altered expression profile of circRNAs in BCLM tissues and 231 liver metastasis cells. Quantitative PCR verified the expression of circRNAs in both BCLM tissues and 231 liver metastasis cells. The altered expressed circRNAs were found in BCLM tissues, compared with primary tumor tissues. These circRNAs involved in metastatic related signaling pathways. Hsa_circ_21439 and hsa_circ_11783 were verified to be the most significantly up- and downregulated circRNAs in both BCLM tissues and cells. circRNA/miRNA analysis revealed that has_circ_21439 and has_circ_11783 could act as ‘miRNA sponge’. This study provides a potential diagnosis and therapy targets for BCLM.